PENGARUH KARAKTERISTIK RASIO FINANSIAL DAN FAKTOR MAKROEKONOMI TERHADAP RETURN ON ASSETS BANK KOMERSIAL - Ari Setyowati; Aditya Septiani (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to analyze the factors that affect Return On Assets (ROA) of financial reports to the commercial banking industry listed on the Indonesia Stock Exchange during 2008-2012. ROA helps management to take into account the bank’s overall profitability and aims to measure the ability of bank management in  managing the assets under their cintrol to income. The examined factors of this research are depossit to assets ratio, capital adequacy ratio, net interest margin, nonperforming loans,inflation, gross domestic product and industry production growth as the independence variable and  retun on assets as the dependent variable. The data that was used in this research was secondary data and selected by using purposive sampling method. Research sample are Indonesian commercial banks listed in 2008-2012 at Bursa Efek Indonesia. Based on analytical results shows that only variable net interest margin and nonperforming loans have significant influence toward return on assets, while fifth variable depossits to assets ratio, capital adequacy ratio, inflation, gross domestic product and industry production growth doesn’t have significant influence toward return on assets.